Technology and youth growing up in a digital world - Blair, Sampson Lee; Claster, Patricia Neff; Claster, Samuel M. (Sociological studies of children and youth, 2015)
This volume focuses on the theme of technology and youth; advancements in communication and leisure technologies over the past decade have radically transformed the role of technology in the lives of youth. Around the globe, children and adolescents are often seen as being the first to embrace new technologies, such as new forms of social media. Having a cell phone, once regarded as an adult technology, has become a necessity within youth culture in many societies. Even video games, once limited to stand-alone computers, have become a venue for social gatherings of youth. The rapid pace of technological advancement has brought about profound changes in the very nature of childhood and adolescence. This volume of examines the role of technology in the lives of children and adolescents. Topics addressed include: cyberbullying, video games and aggressive behavior, online gaming and the development of social skills, sexuality, child pornography, virtual communities for children, social networking and peer relations, and other related issues.